Effect of short video addiction on the sleep quality of college students: chain intermediary effects of physical activity and procrastination behavior - Zhao, Zhe; Kou, Yali (Frontiers in Psychology, 2024)
The purpose of this study was to examine the impact of short video addiction on college students' sleep quality and to elucidate the mechanism underlying this relationship. Thus, we examined the correlation between short video addiction and sleep quality and analysed the roles of physical activity and procrastination. Methods: The Short Video Addiction Scale, Pittsburgh Sleep Quality Index, Aitken Procrastination Inventory, and Physical Activity Rating Scale were administered to 337 college students. Data were analysed using SPSS 27.0. Pearson's correlation analysis and mediation analysis using the bootstrapping test were performed for the standard method bias test. Results: (1) Overall, 25.2% of college students had problems with sleep quality (indicated by a PSQI score ≥8). (2) Short video addiction score is positively correlated with college students' sleep quality score; procrastination score was positively associated with both short video addiction score and sleep quality score, and physical activity score was negatively associated with them. (3) Short video addiction significantly positive predicted sleep quality (β=0.458, P<0.001), a significant negative predictive effect on physical exercise (β=-0.183, P<0.001), and a significant positive effect on procrastination behaviour (β=0.246, P<0.001). After physical exercise and procrastination behaviour were entered into the regression equation, short video addiction and procrastination were significantly positive predictors of sleep quality, and physical activity was significantly negative predictor of sleep quality. (4) After accounting for the variables of age, gender, and grade, physical activity and procrastination behaviours independently mediated the association between short-video addiction and sleep quality. Physical activity and procrastination behaviour acted as chain mediators in the association between short video addiction and sleep quality, with a chain mediation effect percentage of 1.04%. Short video addiction directly affects college students' sleep quality, indirectly through physical activity and procrastination behaviour.